1999
DOI: 10.1074/jbc.274.31.21769
|View full text |Cite
|
Sign up to set email alerts
|

The Dihydrolipoamide S-Acetyltransferase Subunit of the Mitochondrial Pyruvate Dehydrogenase Complex from Maize Contains a Single Lipoyl Domain

Abstract: Immunoanalysis of mitochondrial proteins from various plants, using a monoclonal antibody against the maize E2, revealed 50 -54-kDa cross-reacting polypeptides in all samples. A larger protein (76 kDa) was also recognized in an enriched pea mitochondrial PDC preparation, indicating two distinct E2s. The presence of a single lipoyl-domain E2 in Arabidopsis thaliana was confirmed by identifying a gene encoding a hypothetical protein with 62% amino acid identity to the maize homologue. These data suggest that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…In contrast, only the smaller of the two proteins has been found in the monocot PDC enzyme and genome searches have suggested that the longer gene lineage is absent from monocots (Thelen et al, 1999). At a genomic level, multigene and multigenome approaches to identify the closest living relatives of flowering plants have confirmed the molecular distinction between dicot and monocot species (Qiu et al, 1999;Soltis et al, 1999;Daly et al, 2001), which was previously based largely on phenotypic traits.…”
Section: Aox1amentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast, only the smaller of the two proteins has been found in the monocot PDC enzyme and genome searches have suggested that the longer gene lineage is absent from monocots (Thelen et al, 1999). At a genomic level, multigene and multigenome approaches to identify the closest living relatives of flowering plants have confirmed the molecular distinction between dicot and monocot species (Qiu et al, 1999;Soltis et al, 1999;Daly et al, 2001), which was previously based largely on phenotypic traits.…”
Section: Aox1amentioning
confidence: 69%
“…Antimycin A-treated suspension cells Potato Aox1/Aox0 Green tissue, root tissue, chloramphenicol-treated and aged tuber, not fresh tuber McIntosh (1990, 1994); Hiser et al (1996) Not induced in a mutant lacking mitochondrial complex III activity are incorporated into the active PDC enzyme Thelen et al, 1999). In contrast, only the smaller of the two proteins has been found in the monocot PDC enzyme and genome searches have suggested that the longer gene lineage is absent from monocots (Thelen et al, 1999).…”
Section: Aox1amentioning
confidence: 99%
“…c Gel in which the protein was identified from spots on the acidic or basic halves of the 2-DE gels of the crude (CA, CB) or pure 80S (PA, PB) fractions, as well as the number of times each protein was identified on the respective gel half. and has been shown to form 28 nm pentagonal dodecahedrons of $2.7 MDa (Thelen et al, 1999).…”
Section: Detecting Proteins That Associate With the Plant Ribosomementioning
confidence: 99%
“…Based upon rate-zonal centrifugation, the maize mitochondrial PDC was previously estimated to be greater than 5 MDa in size, 55 due in part to a 2.7 MDa pentagonal dodecahedron central core of dihydrolipoamide acetyltransferase subunits. 56 The quaternary structure and organization of the plastid PDC is largely unknown because the plastid PDC, unlike the mitochondrial form, dissociates rapidly in vitro. 57 The presence of all four subunits in the membrane-depleted 30k × g fraction characterized here (bands [17][18][19][20][21][25][26][27] indicates this complex can be isolated under rapid extraction conditions for further structural analyses (Table 2).…”
Section: Phinney and Thelenmentioning
confidence: 99%